If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + x = 26 Reorder the terms: x + 7y = 26 Solving x + 7y = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. x + 7y + -7y = 26 + -7y Combine like terms: 7y + -7y = 0 x + 0 = 26 + -7y x = 26 + -7y Simplifying x = 26 + -7y
| 16x-3+3x-5=-3x-63 | | 5(9x+4)=290 | | (300-x)100=110 | | 4(3n+4)=2(6n+8) | | y-9x=22 | | 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x | | y=7500-9.5(8000) | | y=7500-9.5(10000) | | 25m=75 | | y=75000+9.5x | | 27+8=10 | | 4(C-9)C=15 | | 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 |